STUDENT KNOWLEDGE ASSESSMENT RATING SYSTEM - O.A. Permyakov; N.I. Zelenkova; L.V. Hryhorenko (Academy of Cognitive and Natural Sciences, 2007)
In article theoretical questions of rating system of an estimation of knowledge ofpupils are examined: development of the conceptual device, main principles, functions, kinds and forms, plus and the minuses inherent given system.